Impact of metabolic syndrome on lipid target achievements in the Arabian Gulf: findings from the CEPHEUS study. Issue 1 (December 2016) - Al-Zakwani, Ibrahim; Al Mahmeed, Wael; Shehab, Abdullah; Arafah, Mohamed; Al-Hinai, Ali; Al Tamimi, Omer; Al Awadhi, Mahmoud; Al Herz, Shorook; Al Anazi, Faisal; Al Nemer, Khalid; Metwally, Othman; Alkhadra, Akram; et al.
Abstract Background The aim of this study was to determine the impact of metabolic syndrome (MetS) on lipid target achievements in the Arabian Gulf. Methods The centralized pan-middle east survey on the undertreatment of hypercholesterolemia (CEPHEUS) included 4171 high and very high atherosclerotic cardiovascular disease (ASCVD) risk patients from six Arabian Gulf countries. Analyses were performed using univariate statistics. Results The overall mean age was 57 ± 11 years, 41 % were females and 71 % had MetS. MetS patients were less likely to attain their HDL-C (34 vs. 79 %;P  < 0.001), LDL-C (27 vs. 37 %;P  < 0.001), non HDL-C (35 vs. 55 %;P  < 0.001) and Apo B (35 vs. 54 %;P  < 0.001) compared to those without MetS. Within the MetS cohort, those with very high ASCVD risk were less likely to attain their lipid targets compared to those with high ASCVD risk [HDL-C (32 vs. 41 %;P  < 0.001), LDL-C (24 vs. 43 %;P  < 0.001), non HDL-C (32 vs. 51 %;P  < 0.001) and Apo B (33 vs. 40 %;P  = 0.001)]. In those with MetS and very high ASCVD risk status, females were less likely to attain their HDL-C (27 vs. 36 %;P  < 0.001), LDL-C (19 vs. 27 %;P  < 0.001) and Apo B (30 vs. 35 %;P  = 0.009) compared to males. Conclusions MetS was associated with low lipid therapeutic targets. Women and those with very high ASCVD risk were also less likely to attain their lipid targets in the Arabian Gulf.